2019
DOI: 10.1371/journal.pone.0225189
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of psychoactive substances in prison: Between initiation and improvement, what trajectories occur after incarceration? COSMOS study data

Abstract: BackgroundFew studies have examined the consumption trajectories of inmates after entry to prison. The aim of this study was to assess the changes in the consumption of psychoactive substance between the period before detention and during incarceration and to characterize the profiles of prisoners with similar consumption trajectories during incarceration.Methods and findingsA multicenter, cross-sectional study was performed in all of the prisons from one region of France. All prisoners incarcerated during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
4
9
1
3
Order By: Relevance
“…The rates of alcohol use could not be compared because different types of use were assessed in the two studies. Consequently, except for stimulants, our results are in line with previous data, even if two elements significantly differed between our study and that of Rousselet et al [28]: the sample (Rousselet et al [28] recruited both men and women) and the study design (the interview was conducted during the third month of incarceration in the work of Rousselet et al [28]).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rates of alcohol use could not be compared because different types of use were assessed in the two studies. Consequently, except for stimulants, our results are in line with previous data, even if two elements significantly differed between our study and that of Rousselet et al [28]: the sample (Rousselet et al [28] recruited both men and women) and the study design (the interview was conducted during the third month of incarceration in the work of Rousselet et al [28]).…”
Section: Discussionsupporting
confidence: 92%
“…After adjustment for sociodemographic features, past-year substance use rates remain in the same gap range. In a previous study in France by Rousselet et al [28], the reported rates of use before incarceration were 49.0% of the respondents (vs. 45.6% in our study) for cannabis, 8.9% for heroin (vs. 9.4% for illegal opioids in our study), and 16.5% for cocaine (vs. 8.6% for stimulants in our study). The rates of alcohol use could not be compared because different types of use were assessed in the two studies.…”
Section: Discussionsupporting
confidence: 59%
“…Given this scenario, we identified a significant prevalence of substance abuse consumption in the lives of PDLs, mainly alcohol, tobacco, marijuana and cocaine/crack. Marijuana is the most commonly consumed illicit substance, corroborating the national and international literature 14 , 31 , with prevalence rates much higher than those observed among the general Brazilian population (marijuana 7.7%, cocaine 3.1%, crack 0.9%) 32 . Marijuana was the most commonly used illicit drug, followed by cocaine/crack and inhalants, and about a quarter had used hypnotics, hallucinogens, opioids and amphetamines or ecstasy, corroborating international studies that point to marijuana as the most commonly used illicit drug among PDLs 33 .…”
Section: Discussionsupporting
confidence: 74%
“…One study found similar results whose marijuana use was reported by 67.5% of PDLs with onset at the age of ten to 15 years 34 . Cannabis is the most commonly consumed illicit substance and can act as a “gateway” to other, heavier drugs 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation